Dynamics of Population in the United States - Hankins, F. H. (Quarterly Journal of Economics, 1935)
Journal Article Dynamics of Population in the United States Get access F. H. Hankins F. H. Hankins Smith College Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 50, Issue 1, November 1935, Pages 164–173, https://doi.org/10.2307/1882347 Published: 01 November 1935